Mediation Model of BPK Recommendation Follow-Ups on Local Government Financial Performance In South Kalimantan - Thofan Iriawan; Prasetyo Yuli Usaid (Keizai, 2025)
This study aims to analyze the influence of regional expenditure and audit findings on the financial performance of local governments in South Kalimantan Province, with the follow-up of Audit Board (BPK) recommendations as a mediating variable. The phenomenon indicates that increased budget allocations have not been fully accompanied by strengthened financial management quality, as evidenced by persistent material audit findings and low follow-up completion rates, which remain below 90%. The research employs a quantitative approach using secondary data sourced from the Audit Result Reports and Local Government Financial Statements of all regencies and cities in South Kalimantan for the period [Insert Years]. Data analysis was performed using PLS-SEM. The results demonstrate that regional expenditure has a positive effect on financial performance but does not significantly influence the follow-up of BPK recommendations. Audit findings are proven to have a negative impact on financial performance but do not significantly affect the follow-up of recommendations. Furthermore, the follow-up of BPK recommendations was found to have no significant effect on financial performance and failed to function as a mediating variable in this research model. This indicates a gap between formal administrative compliance and substantial improvements in governance quality. This study provides an empirical contribution to public sector accounting literature regarding the complex relationship between audit and fiscal dynamics at the regional level. Local governments are advised to strengthen bureaucratic capacity and internal oversight functions to ensure that the follow-up of audit results serves not merely as a regulatory formality but as a strategic driver for sustainable financial performance system.